A emergência dos Bric no cenário internacional - Cunha, Claussia Neumann da (Universidade do Vale do Rio dos Sinos, 2010)
This paper highlights the importance of paradigm established by BRIC stands for International Negotiations, highlighting the strategic role that these four Nations have in this environment of global competitiveness. The fundamental aspects of relationships and actions of the BRIC competitive on the international agenda, as a strategic alliance aimed at cooperation, with focus towards greater integration in the international arena, will be detailed. The objective of this study is focused on the international growth strategies analysis of BRIC, its most distinct areas and territories, its evolution since the establishment of the term by Jim O'Neill, his contribution to the development of countries entered and its possible influenced the drafting of a new group capable of changing international relations, giving special attention to their relations in international trade and the possibility of creating an effective group. In conclusion, the answers are presented – both in theory and in practice – to the challenges as well as the future prospects for cooperation and growth of the BRIC group in the new international order that is emerging in the twenty-first century.

Se argumenta en este trabajo la importancia que tiene BRIC para las negociaciones internacionales, destacando el papel estratégico que estas cuatro naciones tienen en la competitividad mundial. Se estudian los aspectos fundamentales de las relaciones y acciones competitivas de BRIC en la agenda internacional, como una alianza estratégica que apunta a la cooperación, con un foco de una mayor inserción en el escenario internacional. El objetivo de este trabajo está en el enfoque de análisis de las acciones de crecimiento internacional de BRIC, con una atención especial a sus relaciones en el comercio internacional y la posibilidad de crear un grupo eficaz. así como las perspectivas de futuro para la cooperación y el crecimiento del grupo BRIC en el nuevo orden internacional que está surgiendo en el siglo XXI.. Por fin, se presentan las respuestas – en la teoría y en la práctica – a los desafíos, así como las perspectivas futuras para la cooperación y el crecimiento del grupo BRIC en la nueva orden internacional que está surgiendo en el siglo XXI
Keywords: BRIC; Cooperação internacional; Países emergentes; Nova ordem internacional; BRIC; International cooperation; Countries emerging; New international order; BRIC; Cooperación internacional; Países emergentes; Nueva orden internacional